MedAlmighty: enhancing disease diagnosis with large vision model distillation - Ren, Yajing; Gu, Zheng; Liu, Wen (Frontiers in Artificial Intelligence, 2025)
IntroductionAccurate disease diagnosis is critical in the medical field, yet it remains a challenging task due to the limited, heterogeneous, and complex nature of medical data. These challenges are particularly pronounced in multimodal tasks requiring the integration of diverse data sources. While lightweight models offer computational efficiency, they often lack the comprehensive understanding necessary for reliable clinical predictions. Conversely, large vision models, trained on extensive general-domain datasets, provide strong generalization but fall short in specialized medical applications due to domain mismatch and limited medical data availability.MethodsTo bridge the gap between general and specialized performance, we propose MedAlmighty, a knowledge distillation-based framework that synergizes the strengths of both large and small models. In this approach, we utilize DINOv2—a pre-trained large vision model—as a frozen teacher, and a lightweight convolutional neural network (CNN) as the trainable student. The student model is trained using both hard labels from the ground truth and soft targets generated by the teacher model. We adopt a hybrid loss function that combines cross-entropy loss (for classification accuracy) and Kullback-Leibler divergence (for distillation), enabling the student model to capture rich semantic features while remaining efficient and domain-aware.ResultsExperimental evaluations reveal that MedAlmighty significantly improves disease diagnosis performance across datasets characterized by sparse and diverse medical data. The proposed model outperforms baselines by effectively integrating the generalizable representations of large models with the specialized knowledge from smaller models. The results confirm improved robustness and accuracy in complex diagnostic scenarios.DiscussionThe MedAlmighty framework demonstrates that incorporating general-domain representations via frozen large vision models—when guided by task-specific distillation strategies—can enhance the performance of lightweight medical models. This approach offers a promising solution to data scarcity and domain gap issues in medical imaging. Future work may explore extending this distillation strategy to other medical modalities and incorporating multimodal alignment for even richer representation learning.